Journalists’ Knowledge and Utilisation of the Freedom of Information Act (FOIA) in Combatting Corruption in Nigeria - Ahmed, Isa; Idi, Shadrach (Darul Yasin Al Sys, 2025)
This study investigated journalists' knowledge and utilization of the Freedom of Information Act (FOIA) in Taraba State, Nigeria, particularly in relation to its role in exposing corruption in governance. Employing a quantitative research approach with a descriptive survey design, the study targeted 144 registered journalists, from which a sample of 84 respondents was selected using stratified and random sampling techniques. Data were collected through face-to-face administration of a questionnaire, ensuring content validity through expert review and confirming reliability via a pilot study. The findings revealed that while journalists in Taraba State possess a moderate level of awareness regarding the FOIA, their understanding of its provisions and practical application remains limited. The utilization of the FOIA to combat corruption was found to be low, with many journalists rarely using the law to expose corruption. Challenges such as bureaucratic delays, resistance from government officials, insufficient information, political pressures, and the complex process of requesting data under the FOIA were identified as major barriers to its effective use. The study recommends training for journalists on the FOIA, improvements in government response processes, stronger legal protections for journalists.